Application of response surface methodology to absorptive separation of SO2 from its mixture with air using marble waste. Issue 4 (2nd April 2020) - Kumar, Lokesh; Jana, Susanta Kumar; Datta, Dipaloy
Abstract: Absorptive separation of SO2 from its mixture with air was studied in a semi-batch bubble column reactor using marble waste (MARWAS) slurry as the absorbent. Scanning electron microscopy with energy-dispersive spectroscopy (SEM/EDS), thermogravimetric analyzer (TGA), and Fourier transform infrared spectroscopy (FTIR) were used to characterize the MARWAS sample. The effects of concentration of SO2 in the feed gas (500–1500 ppm), batch-volume of the slurry (250–450 mL), flow rate of gaseous mixture (20–40 L/min), and initial solids loading (1–3 g) on the percent SO2 removal efficiency (PRE) and slurry saturation time (SST) were studied. Response surface methodology was used to optimize the process parameters. The optimal conditions for absorption of SO2 were 750 ppm, 400 mL, 25 L/min, and 2.5 g. The corresponding experimental values of PRE and SST were 99.49% and 29.56 min, respectively. Experimental data collected under optimal conditions could be adequately fitted to quadratic models for the responses PRE and SST with the respective R 2 values of 0.9562 and 0.9959. The developed models, therefore, predicted a reasonably accurate (<5% error) assessment of optimal conditions for separation of SO2 using MARWAS slurry. The results of the present study can be usefully employed for desulfurization of flue gases.